'Just notes': Young musicians' perspectives on learning expressive performance. (October 2021) - Meissner, Henrique; Timmers, Renee; Pitts, Stephanie E
Expressiveness is an important aspect of an excellent music performance as it adds quality and interest to the playing and listening experience. Although several studies have investigated tertiary students' learning of expressiveness, little is known about effective approaches for teaching children to perform expressively. In the present project, 16 young musicians (aged 9–16, with performance levels at Pre-Grade 1 – Grade 8) took part in a video-stimulated recall interview after an experimental investigation which had featured methods for teaching and facilitating expressiveness. The interviews explored pupils' perspectives on that instruction, which included practice of difficult sections, scales practice, improvisation, and questions and dialogue regarding musical character. Participants who had been taught via dialogic teaching indicated that the questions relating to musical character and expressive tools had been helpful for their understanding of the 'musicality' of their pieces and thus for their learning of performance expression. The questions regarding musical character were seen as helpful, as this had facilitated pupils' reflection on, and understanding of the interpretation, thus contributing to their learning of expressiveness. This demonstrates the importance of teachers' enquiry and pupils' reflection for young musicians' learning of expressive performance.